PENGARUH LATAR TERHADAP TERBENTUKNYA WATAK TOKOH DALAM ROMAN ANTROPOLOGIS NAMAKU TEWERAUT KARYA ANI SEKARNINGSIH - Asmabuasappe NFN (Balai Bahasa Provinsi Papua, 2019)
The characters formation can not be separated from the background that exert an influence on lived of a community. Likewise, the character of the Asmat’s people that strongly influenced by historical background, such as physical and social setting. The disclosure of influence on the formation of figure character in novel Namaku Teweraut by Ani Sekarningsih using objective methods. The result of this analysis showed that the physical setting and social setting were greatly affect to the formation of the figure characters in the novel Namaku Teweraut. Those characters were anger, generous, helpful, unruly, tough, brave, and adroit.